OPT.IMASI ALAT ANGKUT PENGIRIMAN BERAS (Studi Kasus pada PT. Umbul Berlian Semarang) - Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2012)
PT. Umbul is a company that has a business renting out vehicles that haul trucks. PT. Dolog is one of the companies that use the services of PT. Umbul is using his truck to transport rice from Warehouse to Warehouse Rice Rice one another in Central Java. PT. Umbul had 5 trucks with a total of 54 trucks. The selection of trucks that will be used by PT. Umbul to transport rice-optimal (selected exceeds the capacity of the truck that transported rice, so many empty trucks). To solve this optimization problem, the method used Integer Linear Programming. Decision variables for this problem are the number of truck type i for transporting rice to Rice Warehouse (GB) or j Xij. Objective function is to minimize the cost of shipping the rice. As for the limiting, the demand of rice for each Warehouse Rice (GB) and hours of operation of the truck. On 4 April 2011, to send rice to GB1 used trailer used by 1 unit, the GB2 is used as one single unit trucks, used trucks to GB3 trailer regular increments of 1 unit, the GB4 use regular trailer 2 units to GB5 used trailer 2 units to be used GB6 trailer trailer 1 unit, and the little ankle GB7 used truck 1 unit and trailer 1 unit. Distribution of the results in the shipping cost of Rp 30,833,050, -   Keywords: Optimization, transportation, integer linear programming